Acetyl-CoA carboxylase inhibition alters tubulin acetylation and aggregation in thrombin-stimulated platelets. (14th October 2021) - Octave, M; Pirotton, L; Ginion, A; Robaux, V; Lepropre, S; Kautbally, S; Darley-Usmar, V M; Ambroise, J; Guigas, B; Giera, M; Foretz, M; Bertrand, L; et al.
Abstract: Introduction: Acetyl-CoA carboxylase (ACC), the first enzyme regulating lipid synthesis, promotes thrombus formation by increasing platelet phospholipid content. Inhibition of its activity decreases lipogenesis and increases the content in acetyl-CoA which can serve as a substrate for protein acetylation. This posttranslational modification plays a key role in the regulation of platelet aggregation, via tubulin acetylation. Purpose: To demonstrate that ACC inhibition may affect platelet functions via an alteration of lipid content and/or tubulin acetylation. Methods: Platelets were treated 2 hours with CP640.186, a pharmacological ACC inhibitor, prior to thrombin stimulation. Platelet functions were assessed by aggregometry and flow cytometry. Lipogenesis was measured via 14C-acetate incorporation into lipids. Lipidomics analysis was carried out on the commercial Lipidyzer platform. Protein phosphorylation and acetylation were evaluated by western blot. Results: Treatment with CP640.186 drastically decreased platelet lipogenesis. However, the quantitative lipidomics analyses showed that preincubation with the compound did not affect global platelet lipid content. Interestingly, this short-term ACC inhibition was sufficient to increase tubulin acetylation level, at basal state and after thrombin stimulation. It was associated with an impaired platelet aggregation, in response to low thrombin concentration, while granules secretion was not affected. Mechanistically, we highlighted a decrease in Rac1 activity, associated with a reduced phosphorylation of its downstream effector PAK2. Surprisingly, actin cytoskeleton was not impacted but we evidenced a significant decrease in ROS production which could result from a decreased NOX2 activity. Conclusion: Pharmacological ACC inhibition decreases platelet aggregation upon thrombin stimulation. The mechanism depends on increased tubulin acetylation, with subsequent alteration of the Rac1/PAK2/NOX2 signaling pathway Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Fonds pour la formation à la Recherche dans l'Industrie et l'Agriculture (FRIA)